PENGARUH PANDEMI COVID-19 TERHADAP PENJUALAN UMKM - Maynanda Maynanda; Ega Rahmawati; Akhmad Sabil; Dawam Mukhlish; Dwi Yuli Rakhmawati (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
2020 is the year when the COVID-19 pandemic spreads to Indonesia. The Indonesian government is trying to prevent the spread of the COVID-19 virus by establishing PSBB and PPKM. The current PPKM policy affects the accommodation and sales sectors due to the lack of space to operate. This resulted in a decrease in revenue in sales. The marketing mix is ​​a marketing component that is effectively used in the business of selling culinary, fashion, services, and online shops. This study aims to determine the effect of the marketing mix on the influence of UMKM sales in the COVID-19 pandemic situation. The marketing mix studied included; products, promotions, people and processes. This research model is a case study by choosing UMKM as the object of this research. This research was conducted in the areas of Sidoarjo and Lamongan where there are UMKM sales under study. Data collection was taken using a survey method by distributing questionnaires to 43 respondents who sold UMKM. The sample collection method used is based on a non-probability technique, namely the convenience sampling technique. Data collection through a questionnaire took place for two days on 21-22 September 2021. The analytical method used is simple linear regression analysis and analyzed through the SPSS tool. The results found from the research are variable X is the COVID-19 pandemic while variable Y is the result of increasing UMKM sales or not.